IMPLEMENTASI PROBLEM BASED LEARNING BERBANTUAN MEDIA FLIPBOOK PADA MATERI AKTIVITAS MASYARAKAT MASA LALU - Nanda Lestari (Sosiolium: Jurnal Pembelajaran IPS, 2024)
Learning outcomes are an important indicator that reflects the level of understanding and achievement of students in a particular subject or skill. Based on observations made in class VII-C of SMP N 27 Semarang, problems were found where students had low learning outcomes in Social Sciences (IPS) subjects. This is shown by the score data in the Natural Resources chapter where 28 students were declared incomplete out of a total of 31 students. This Classroom Action Research (PTK) aims to analyze the application of the Problem Based Learning learning model assisted by Flipbook learning media in improving learning outcomes in social studies subjects in class VII-C students at SMP N 27 Semarang. Data collection methods are carried out through test, observation and documentation techniques. In this research, it was found that the application of the Problem Based Learning model assisted by Flipbook learning media could improve the learning outcomes of class VII-C students at SMP N 27 Semarang. In cycle I, 32 percent of students were declared complete and this increased by 45 percent in cycle II to 77 percent.